1997
DOI: 10.1093/mutage/12.4.201
|View full text |Cite
|
Sign up to set email alerts
|

Extruded micronuclei induced by colchicine or acrylamide contain mostly lagging chromosomes identified in paintbrush smears by minor and major mouse DNA probes

Abstract: In the mouse bone marrow micronucleus assay, it was studied whether micronuclei (MN) could be expelled from polychromatic erythrocytes (PCE) in a similar way to the main nucleus. To avoid the disrupting centrifugation step of the conventional bone marrow preparation procedure, the paintbrush technique was used in the present experiments. With May-Grunwald-Giemsa staining of paintbrush slides, 5 % of the colchicine (COL)-induced MN were found attached to the outside membranes of PCE and were regarded as extrude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In [Schriever-Schwemmer and Adler, 1994;Schriever-Schwemmer et al, 1997;Attia et al, 2003;Attia, 2007]. However, the finding that 29.3% of the MN had no FISH signals seems to be higher than the 20.7% reported by Jie and Jia [2001] for the control.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…In [Schriever-Schwemmer and Adler, 1994;Schriever-Schwemmer et al, 1997;Attia et al, 2003;Attia, 2007]. However, the finding that 29.3% of the MN had no FISH signals seems to be higher than the 20.7% reported by Jie and Jia [2001] for the control.…”
Section: Discussionmentioning
confidence: 70%
“…The negative control groups received PBS only, while the positive control groups were injected intraperitoneally with either 2 mg/kg mitomycin C (MMC; Sigma) or 2 mg/kg colchicine (COL; Sigma). The doses for the positive controls were chosen by reference to earlier in vivo studies [Schriever-Schwemmer and Adler, 1994;Schriever-Schwemmer et al, 1997;Attia et al, 2003;Attia, 2007]. The doses of lomefloxacin were selected on the basis of their effectiveness in inducing chromosomal alterations in mouse bone marrow [Singh et al, 2003].…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…is similar to those employed for MN induction in mouse bone marrow (i.p. treatments) by spindle poisons [27,28].…”
Section: Colchicine Experimentsmentioning
confidence: 99%
“…It has also recently been found that red blood cells can also be micronucleus excreted. And the micronuclei to be discharged mainly originate from the whole chromosome [24].…”
Section: Demonstration Of the Program 221 Selection Of Experimentalmentioning
confidence: 99%